2013
DOI: 10.3109/17453674.2013.792030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in walking and running in patients with hip dysplasia

Abstract: Background and purpose Earlier studies have suggested that the hip extension angle and the hip flexor moment in walking are affected by hip dysplasia, but to our knowledge there have been no reports on running or evaluations of self-reported health. We evaluated differences in walking, running, and self-reported health between young adults with symptomatic hip dysplasia and healthy controls.Patients and methods Walking and running in 32 patients with hip dysplasia, mean 34 (18–53) years old, was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 25 publications
3
45
2
Order By: Relevance
“…Some prior studies reported a marked decrease in peak hip extension in patients, which was not a finding with our cohort (Jacobsen et al, 2013; Romano et al, 1996; Skalshoi et al, 2015). It has been postulated that reduced hip extension is a pain avoidance mechanism to reduce anterior joint loading (Skalshoi et al, 2015).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Some prior studies reported a marked decrease in peak hip extension in patients, which was not a finding with our cohort (Jacobsen et al, 2013; Romano et al, 1996; Skalshoi et al, 2015). It has been postulated that reduced hip extension is a pain avoidance mechanism to reduce anterior joint loading (Skalshoi et al, 2015).…”
Section: Discussioncontrasting
confidence: 96%
“…Results from these studies support the concept that dysplasia alters hip kinematics and kinetics during gait, but data have been contradictory. For example, Romano et al (1996) and Jacobsen et al (2013) found lower peak hip extension during stance in patients with dysplasia, whereas Pederson et al (2004) found no significant differences in hip extension during stance.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, identical kinematics were used for both subject groups. In previous studies, dysplastic patients exhibited subtle alternations in kinematics during gait, including increased pelvic drop, increased pelvic rotation, reduced hip extension and a reduction in ground reaction force in comparison to normal hips [49, 50]. Increased pelvic drop may cause increased labral loading, while increased pelvic rotation may shift contact patterns posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Transsartorial periacetabular osteotomy (PAO) [24] is performed in young patients with hip dysplasia to relieve hip pain and increase hip-related physical function [5,6]. Use of PAO may help postpone or prevent hip osteoarthritis (OA), but to our knowledge, no studies randomizing patients to either PAO or conservative treatment have been done, therefore we do not know whether PAO directly affects the development or progression of OA in patients with hip dysplasia.…”
Section: Introductionmentioning
confidence: 99%